2018
DOI: 10.1038/s41467-018-07748-z
|View full text |Cite
|
Sign up to set email alerts
|

Latin Americans show wide-spread Converso ancestry and imprint of local Native ancestry on physical appearance

Abstract: Historical records and genetic analyses indicate that Latin Americans trace their ancestry mainly to the intermixing (admixture) of Native Americans, Europeans and Sub-Saharan Africans. Using novel haplotype-based methods, here we infer sub-continental ancestry in over 6,500 Latin Americans and evaluate the impact of regional ancestry variation on physical appearance. We find that Native American ancestry components in Latin Americans correspond geographically to the present-day genetic structure of Native gro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
179
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(194 citation statements)
references
References 53 publications
14
179
0
1
Order By: Relevance
“…Approximately 50% of mainland Chileans perceive themselves as predominantly of European ancestry ( Adhikari et al, 2017 ), and similarly, the Robinson Crusoe Islanders self-identify as European ( Villanueva et al, 2014 ). Our results, similar to studies on mainland Chile ( Adhikari et al, 2017 ; Chacon-Duque et al, 2018 ), indicate the islanders have a substantial genetic contribution from indigenous admixture.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Approximately 50% of mainland Chileans perceive themselves as predominantly of European ancestry ( Adhikari et al, 2017 ), and similarly, the Robinson Crusoe Islanders self-identify as European ( Villanueva et al, 2014 ). Our results, similar to studies on mainland Chile ( Adhikari et al, 2017 ; Chacon-Duque et al, 2018 ), indicate the islanders have a substantial genetic contribution from indigenous admixture.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings estimate the genetic contribution from indigenous South Americans to the RC Island population at 46.9%, similar to both Chilean controls (43.4%) and Chile_GRU non-indigenous controls (49.1%). Previous research in outbred Chilean populations identified 40–45% indigenous admixture with European and African estimated at 49–52 and 3% respectively ( Eyheramendy et al, 2015 ; Adhikari et al, 2017 ; Lorenzo Bermejo et al, 2017 ; Chacon-Duque et al, 2018 ). At the autosomal level, we were unable to clearly distinguish between Iberian (IBS) and European (CEU) ancestry at this level of resolution in the RCI population.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Rather, HL groups encompass an extraordinarily diverse set of populations, which are characterized by distinct combinations of ancestry from Africa, Europe, and the Americas [23][24][25][26][27]. Additionally, the Native American component of HL ancestry varies substantially according to the regional origins of the populations [28,49,50]. With this in mind, we have been investigating the contributions of ancestry to genetic risk and T2D health disparities in diverse HL populations.…”
Section: Diabetes Prevalence and Population Disparitiesmentioning
confidence: 99%
“…These methods describe kinship or haplotype sharing with the reference. This, in turn, can be used to learn an individual's ancestry mixture, which is routinely done for example via Non-Negative Least Squares (NNLS) (Hellenthal et al, 2014;Pagani et al, 2016) or SOURCEFIND (Chacón-Duque et al, 2018). Because the computational cost of these approaches is linear in the size of the target dataset, they can be used at the biobank scale.…”
Section: Mixtures Of Known Populationsmentioning
confidence: 99%